Aplikasi Metode Taguchi untuk mengetahui Kualitas Kopi Sangrai Liberika berdasarkan Parameter Peyangraian: Taguchi - Roni Novison; Rianda Dwi Sapta (Politeknik Caltex Riau, 2021)
Abstract Currently there are still several processes in coffee roasting that still use the traditional way of using a pan made of iron, so it took a long time to roast it and is also less efficient because of the uneven heat generated. One of the processes carried out to simplify the roasting process is by making a coffee roaster using a heater and an electric motor. This heater serves to heat the roasting room so that the heat obtained is evenly distributed throughout the roasting room. Also added is the setting in temperature and motor speed so that the taste of the coffee is more delicious. In this roasting process using the taguchi method so that data retrieval is more efficient with 9 variable experiments where the roasting temperature is 240 ℃, 250 ℃ and 260 ℃. Roasting time used is 30, 40 and 50 minutes. Roasting speed at 20 RPM, 40 RPM and 60 RPM. The power electricity used in the process of roasting is 296,96 watt, the calorocity rate of the calor 288,96 J/s. heat (Q) 494,016 and energy 475.200 joule. Where based on the variable SN ratio value of 260 ℃, the frying time of 60 minutes and the roasting speed of 60 RPM occupy the best roasting at reducing water content and acidity (pH) Keywords: Roasting Coffee, heater, DC Motor, Taguchi, SN Ratio